Economic evaluation of offshore storage potential in the US Exclusive Economic Zone. Issue 1 (26th October 2012) - Eccles, Jordan K; Pratson, Lincoln
Abstract Drawing upon previously published results, we evaluate the offshore potential for storing CO2 within marine sediments located inside the US Exclusive Economic Zone (EEZ). We then model the cost for transporting and injecting CO2 into these strata, including into deep‐marine (>3000m water depth) strata that we refer to as being 'self‐sealing' because pressure and temperature regimes would form an overlying gravitational seal. Finally, we compare the integrated transport and injection cost estimates for self‐sealing and non‐self‐sealing offshore storage against the same integrated cost estimates for onshore storage in 15 deep‐saline sandstone aquifers located throughout the continental USA. The comparison is presented in the form of marginal abatement cost curves, which show that ocean storage is likely to be two or more times as expensive as onshore storage: 500 million tonnes of annual CO2 emissions from coal‐fired power plants in the USA is available for <$5/tonne in onshore DSAs, < $10/tonne in non‐self‐sealing offshore strata, and <$15/tonne in self‐sealing offshore strata, with the cost differential between onshore and offshore storage increasing further up the supply curve. The higher total offshore costs are due to a combination of increases in transport and storage costs, with transport costs dominating total costs with increasing distance from shore. This suggests that CO2 capture system operators would have to pay substantially more for offshore geologic storage over onshore options. The cost difference may be mitigated by certain advantages of offshore storage, which could include easier access to property rights, simplified regulation, and possibly lower monitoring, measurement, and verification (MMV) requirements. © 2012 Society of Chemical Industry and John Wiley & Sons, Ltd